Analysis of Quranic Verses on Educational Evaluation (Thematic Approach) - Hafid; Cecep Anwar; Aisyah Alief Dzulfiqrah; Fitri Nurlaeli (al-Afkar, Journal For Islamic Studies, 2025)
Evaluation in the education sector plays a crucial role in measuring the success of the learning process. The position of evaluation is very strategic in the education system. Evaluation is an integral part of human life, especially in education, where assessments from tests taken by students serve as evaluation for educators. In Islamic education, evaluation is essential in assessing students' understanding of Islam and the educators' proficiency in teaching Islamic principles. The Qur'an inspires all fields of knowledge and teaching, including thematic interpretation, which explains evaluation. In tafsir tarbawi, evaluation is also a significant topic. This study aims to analyze the verses of the Qur'an related to educational evaluation through a thematic approach. By examining the thematic interpretation of relevant Qur'anic verses, this research seeks to identify the principles and types of educational evaluation according to Islamic teachings. The findings are expected to provide valuable guidance for educators in implementing effective and meaningful evaluations within the context of Islamic education. The approach used in this study involves an in-depth analysis of Qur'anic verses and a review of relevant literature. The research findings emphasize the importance of integrating religious values into the practice of educational evaluation to shape the character and morality of students in accordance with Islamic.